2021
DOI: 10.1021/acsomega.1c02215
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Residence Time Distribution in Plug Flow Continuous Oscillatory Baffled Crystallizers

Abstract: Heat transfer coefficients in a continuous oscillatory baffled crystallizer (COBC) with a nominal internal diameter of 15 mm have been determined as a function of flow and oscillatory conditions typically used under processing conditions. Residence time distribution measurements show a near-plug flow with high Peclet numbers on the order of 100–1000 s, although there was significant oscillation damping in longer COBC setups. Very rapid heat transfer was found under typical conditions, with overall heat transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…They found that the attained oscillatory amplitude is halved at the outlet when 11 U-bends and 22 columns are used. 12 From previous computational fluid dynamic (CFD) evaluations (data not shown and unpublished), the Ubend is suspected to have more of an influence on oscillatory dampening than that of the baffle constrictions. This is due to momentum changes and collision of eddies along a nonsymmetrical pathway around U-bend radii and fluid traveling at different distances.…”
Section: Change Of Rtd Across the Reactor Lengthmentioning
confidence: 97%
See 3 more Smart Citations
“…They found that the attained oscillatory amplitude is halved at the outlet when 11 U-bends and 22 columns are used. 12 From previous computational fluid dynamic (CFD) evaluations (data not shown and unpublished), the Ubend is suspected to have more of an influence on oscillatory dampening than that of the baffle constrictions. This is due to momentum changes and collision of eddies along a nonsymmetrical pathway around U-bend radii and fluid traveling at different distances.…”
Section: Change Of Rtd Across the Reactor Lengthmentioning
confidence: 97%
“…These plots are similar to figures made of other multipass OBR setups, exhibiting minimal axial dispersion. 12,33 3.4. Scaling the OBR for Bioprocesses.…”
Section: Change Of Rtd Across the Reactor Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, an oscillatory flow crystallizer (OFC) has been considered to be a promising candidate to avoid mechanical agitation effects, as it can generate recirculation flow and vortex through the combination of a reactor structure and oscillation process . This unique flow can create a series of well-mixed volumes, which is beneficial to control mass and heat transfer. Furthermore, the appropriate residence time in the OFC can also improve the quality of the crystals produced. It is certain that the employment of the OFC for crystallization can reach the requirement of flow field mixing; however, the principle on how to balance the relationship between the stable environment and appropriate disturbance has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%